Correction of clothing insulation for movement and wind effects, a meta-analysis - George Havenith; Hakan O. Nilsson (2004)
A meta-analysis of the effect of body and air movement on the insulation provided by workwear and cold-weather clothing [1.22 clo (0.189 m 2 °C W −1)